Human Rights, Procedural Protections and the Social Construction of Mental Illness: Involuntary Civil Commitment under China’s New Mental Health Law - Charlton, Guy; Gao, X. (Melbourne Law School, 2014)
China has been criticised by human rights organisations for its failure to provide sufficient safeguards for involuntary confinement and discharge, involuntary experimental medical trials, and forced treatment of those with mental health problems. The legal shortcomings have become increasingly salient given the growing emphasis on the civil rights of mental health patients across the globe and China’s recent accession to Convention on the Rights of Persons with Disabilities. In an effort to address these domestic problems and international responsibilities, China adopted its first National Mental Health Law in 2012. According to Xinhua state news agency the law seeks to 'curb abuses regarding compulsory mental health treatment and protect citizens from undergoing unnecessary treatment or illegal hospitalization’. The protracted 27 year discussion over funding, oversight responsibilities, admissions criteria, accreditation standards, and community mental health services, has led to a law which seeks to provide one national standard for the delivery and treatment of mental health services as well as standards and safeguards for involuntary commitment. This paper examines the provisions of the law as they relate to the definition of mental disorder and involuntary civil commitment. It argues that the new statute provides some safeguards to prevent unfair or abusive involuntary committal, as well as incorporating additional normative standards (based on international and domestic law) which should provide for additional measures to protect individuals who suffer from mental illness. However, the broad definition of mental illness in the Act could lead to involuntary committal. Likewise, there is a lack of extra-medical or due process safeguards that could enhance the ability of the system to maintain and protect personal dignity. Additional changes are therefore required to enable the Law to reach the standard required under the Chinese Constitution and the Convention.